2017
DOI: 10.1038/s41598-017-08779-0
|View full text |Cite
|
Sign up to set email alerts
|

Tau plasma levels in subjective cognitive decline: Results from the DELCODE study

Abstract: Previous studies have demonstrated increased tau plasma levels in patients with Alzheimer’s disease (AD) and mild cognitive impairment (MCI) due to AD. Much less is known whether increased tau plasma levels can already be detected in the pre-MCI stage of subjective cognitive decline (SCD). In the present study we measured tau plasma levels in 111 SCD patients and 134 age- and gender-matched cognitively healthy controls participating in the DZNE (German Center for Neurodegenerative Diseases) longitudinal study … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 23 publications
5
21
0
1
Order By: Relevance
“…Mattson et al found that higher plasma t-tau was associated with AD dementia and showed a signi cant correlation with worse cognition, more atrophy and more hypometabolism during follow-up in the ADNI study [30]. However, in our study, plasma t-tau showed no signi cant correlation with cognitive function and can not re ect the levels of t-tau in CSF, which is also in line with some previous ndings [30,32].Besides, increasing evidence supports that plasma p-tau is a promising biomarker for AD, which can not only be associated with CSF p-tau but also correlates with amyloid PET uptake and discriminates AD dementia from non-AD neurodegenerative disease, partly re ecting AD pathology and disease severity [33][34]. In this study, due to the low concentration in the samples and methodology limitations, we did not measure p-tau in plasma.…”
Section: Discussionsupporting
confidence: 90%
“…Mattson et al found that higher plasma t-tau was associated with AD dementia and showed a signi cant correlation with worse cognition, more atrophy and more hypometabolism during follow-up in the ADNI study [30]. However, in our study, plasma t-tau showed no signi cant correlation with cognitive function and can not re ect the levels of t-tau in CSF, which is also in line with some previous ndings [30,32].Besides, increasing evidence supports that plasma p-tau is a promising biomarker for AD, which can not only be associated with CSF p-tau but also correlates with amyloid PET uptake and discriminates AD dementia from non-AD neurodegenerative disease, partly re ecting AD pathology and disease severity [33][34]. In this study, due to the low concentration in the samples and methodology limitations, we did not measure p-tau in plasma.…”
Section: Discussionsupporting
confidence: 90%
“…Soluble T-tau proteins were quantitatively measured using the Simoa Tau 2.0 reagent kit (Quanterix), which has been widely used in multiple published studies (see, for example [58][59][60] ). The LLOD and LLOQ are reported as 0.019 and 0.061 pg/mL, respectively.…”
Section: Preparation Of Samples For Mass Spectrometrymentioning
confidence: 99%
“…Regarding tau specifically, a study has shown that increased CSF phosphorylated tau in healthy elderly could predict development of SCD at 3 years, but another study showed that while Aβ42 might decrease in SCD, T-tau and P-tau181 do not change significantly [ 15 , 17 ]. In another study, plasma tau in SCD did not differ from levels in healthy controls, and plasma levels did not correlate with CSF [ 16 ]. In the present study, we observed that core AD biomarkers were lower (Aβ42) or higher (T-tau, P-tau181) in SCD compared to controls, although maintaining a large overlap between the two groups, while N-224 could not distinguish between controls and SCD.…”
Section: Discussionmentioning
confidence: 99%